Estudo clínico randomizado, aberto e comparativo para avaliação de segurança, tolerabilidade e eficácia analgésica de duas diferentes apresentações de medicamento tópico na realização de curetagem dermatológica de molusco contagioso em pacientes pediátricos - Schalka, Sérgio; Addor, Flávia Alvim Sant'Anna; Silva, Vanessa de Melo [UNESP]; Pinto, Patrícia Camarano [UNESP]; Milan, Ana Lúcia Koff; Pannuti, Estela Maia Bellini [UNESP] (My University, 2010)
Aim: This study aimed to compare the safety and analgesic efficacy of a new topical drug (in two different presentations: cream and aerosol) consisting of benzocaine, menthol and triclosan, in the curettage of molluscum contagiosum. Method: The study included 296 volunteers in different stages: 256 healthy adult volunteers for the safety evaluation, and 40 volunteers between 2 and 12 years old who presented Molluscum contagiosum, for the evaluation of tolerability and efficacy. Each volunteer represented two experimental units (left and right) where it was applied randomly the tested products (cream or aerosol) 30 minutes before the dermatological curettage, immediately after and twice a day during 7 days. Dermatological evaluations of safety and efficacy were performed immediately after the procedure, 3 and 7 days after the curettage. Results: During safety evaluation, the tested products showed no irritant, sensitizing, phototoxic or photosensitizing potential. Both presentations, cream and aerosol, were considered safe with no statistically significant differences between them. With respect to analgesic efficacy, the results showed that the medication promoted the reduction of painful symptoms and there was no statistically significant difference (p <0.05) between the two presentations. Conclusion: The tested product, in two different presentations, was considered safe and effective in controlling pain symptoms during and after the curettage of molluscum contagiosum. © Copyright Moreira Jr. Editora.
A randomized, open-label, comparative clinical study for the evaluation of safety, tolerability and analgesic efficacy of two different presentations of topical medication in the treatment of dermatological curettage of molluscum contagiosum in pediatric patients
Keywords: Curettage; Local anesthesia; Molluscum contagiosum; analgesic agent; benzocaine; benzocaine plus menthol plus triclosan; ef 028; menthol; triclosan; unclassified drug; analgesic activity; child; childhood disease; clinical trial; controlled clinical trial; controlled study; drug dosage form comparison; drug efficacy; drug formulation; drug mechanism; drug safety; drug tolerability; human; major clinical study; molluscum contagiosum; open study; photosensitization; phototoxicity; postoperative pain; preschool child; randomized controlled trial; school child; side effect; skin irritation; skin sensitization; skin surgery; treatment duration